TATA CARA PENETAPAN MAHAR PADA PERKAWINAN SUKU NIAS DI DESA PETAPAHAN KECAMATAN TAPUNG KABUPATEN KAMPAR - Ester Sriana Wati ST. Pandiangan; Risdayati " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2022)
This research was conducted on Scavenger in this study the Nias traditional marriage dowry (Bowo) is very mandatory in carrying out traditional Nias marriages. However, along with the times, the dowry (Bowo) is not easy to fulfill because of the large costs that are borne by the men to carry out traditional Nias marriages and the procedures are no longer carried out as a whole in the Nias area and outside Nias (nomads). The subjects studied were 5 people to search for the determination of informants using pourposive sampling technique, where the sample was taken intentionally and in accordance with the criteria determined by the author. The method used in writing this research is qualitative research. The theory used is the theory of tradition and social change.The results obtained from research in the field of dowry provisions in the procedure for carrying out traditional Nias marriages are determined from the degree of social status of the Nias community which is calculated in the form of dowry (Bowo) as a form of acknowledgment of respect and appreciation for the dignity of women, establishing kinship, and preventing divorce.Keywords: Determination of Dowry, Procedure for Continuing Marriage